Efficacy of selective serotonin reuptake inhibitors and adverse events: Meta-regression and mediation analysis of placebo-controlled trials. (February 2016) - Barth, Michael; Kriston, Levente; Klostermann, Swaantje; Barbui, Corrado; Cipriani, Andrea; Linde, Klaus
Abstract : Background: It has been suggested that the efficacy of antidepressants has been overestimated in clinical trials owing to unblinding of drug treatments by adverse events. Aims: To investigate the association between adverse events and the efficacy of selective serotonin reuptake inhibitors (SSRIs). Method: The literature was searched to identify randomised, double-blind, placebo-controlled trials of SSRIs in the treatment of major depression. Efficacy outcomes were response to treatment and change in depressive symptoms. Reporting of adverse events was used as an indicator of tolerability. Random effects meta-analyses were used to calculate pooled estimates. Meta-regression analyses were performed to investigate the association between adverse events and efficacy. Potential mediation was investigated with the Baron & Kenny approach. Results: A total of 68 trials ( n = 17 646) were included in the analyses. In meta-analysis SSRIs were superior to placebo in terms of efficacy (odds ratio, OR = 1.62, 95% CI 1.51–1.72). More patients allocated to SSRIs reported adverse events than did patients receiving placebo (OR = 1.73, 95% CI 1.58–1.89). Meta-regression analyses did not find an association between adverse events and efficacy ( P = 0.439). There was no indication of adverse events mediating the effect of SSRI treatment. Conclusions: Our results do not support, but also do not unequivocally disprove, the hypothesis that adverse events lead to an overestimation of the effect of SSRIs over placebo.